The Role of the Argumentation-Techniques In The Pragmatics Intonations “The Rubble of Time: a woman`s Shattered Body “ Novel by Anisa Aboud - حرفوش, ملاذ; مالك ياسين, (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research exposes the implication meaning in the novel Accor to the argumentation theory، this theory got attention in the linguistic research، because it has a role in an enable intents. This research is studying the novel Accor to the argumentation linguistic study، it supposes that the novel is not just a literary work that has aesthetic structure or a system of ideas and self-realization، indeed، the novel remains above the criticism of the reality، because it’s seek to change the reality، and it’s led to alternative ideas، these ideas should be a strong force in the community. In this novel، the research is test the essence of speech for discover the techniques of the different persuasion، these techniques work to change the position of recipient to get to the purposes of the speech، and we will explain the argumentation purposes that we discovered through analysis this novel.